2012
DOI: 10.7249/wr917
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of World War II on Economic and Health Outcomes across Europe

Abstract: In this paper, we investigate the long-run effects of World War II on socio-economic status (SES) and health of older individuals in Europe. Physical and psychological childhood events are important predictors for labor market and health outcomes in adult life, but studies that quantify these effects in large samples that cover entire diverse populations are still rare. We analyze data from SHARELIFE, a retrospective survey conducted as part of the Survey on Health, Aging, and Retirement in Europe (SHARE) in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 12 publications
7
61
0
1
Order By: Relevance
“…While Currie et al (2015) find no main effect of the unemployment rate on depression, Hispanic mothers showed a significant increase in the probability of being depressed. Similarly, in an earlier paper Kesternich et al (2014) showed exposure to the events of WWII was consistently significantly associated with being more depressed as an adult, higher levels of adult diabetes, and reporting one's subjective health as worse.…”
Section: Physical and Mental Health Effectsmentioning
confidence: 66%
See 1 more Smart Citation
“…While Currie et al (2015) find no main effect of the unemployment rate on depression, Hispanic mothers showed a significant increase in the probability of being depressed. Similarly, in an earlier paper Kesternich et al (2014) showed exposure to the events of WWII was consistently significantly associated with being more depressed as an adult, higher levels of adult diabetes, and reporting one's subjective health as worse.…”
Section: Physical and Mental Health Effectsmentioning
confidence: 66%
“…These external events are not only part of the retrospective accounts but are supplemented by objective data at the time measuring them contemporaneously. The evidence so far indicates good correspondence between the self-reports and the actual events (Smith, 2009b;Kesternich et al, 2014).…”
Section: Getting the Datamentioning
confidence: 86%
“…It also recorded very detailed labour market history including individual job spells and changes in labour market status as well as several main characteristics of all declared jobs and gaps between them. Although retrospective information is an imperfect substitute for contemporaneous data collected over the lifetime, the quality and usefulness of SHARELIFE data have been reflected in a number of publications (for example, Attanasio et al, 2014;B€ orsch-Supan et al, 2011;Kesternich et al, 2014) and there is evidence from this and other surveys on reliability of retrospective data in particular with respect to important major life events (for example, Beckett et al, 2001;Havari and Mazzonna, 2011;Smith and Thomas, 2003). Moreover, while the degree of detail collected in a retrospective survey on each particular period is relatively low, an important advantage of this type of information is that life histories generated on the basis of it do not suffer from panel attrition and can be matched with outcomes that are measured significantly later.…”
Section: Structure Of Share Datamentioning
confidence: 99%
“…There is a growing body of literature showing the significance of major events experienced by individuals in the past for their current socio-economic outcomes in different historical contexts (for example, Attanasio et al, 2014;Cavapozzi et al, 2011;Deindl, 2012;Kesternich et al, 2014). In Section 3 we showed how SHARELIFE data can be used to examine the dynamics of the labour market in Poland at the time of Notes: Sample restricted to respondents who declared working in 1988 in wave 3 with valid information in waves 2 and/or 4.…”
Section: Analyzing Long-term Consequences Of Economic Shocksmentioning
confidence: 99%
“…SHARE covers representative samples of the population aged 50 and over in 13 European countries, with about 20,000 observations. In this analysis, we concentrate on Germany which was not only among the countries most directly affected by World War II in general but also by hunger associated with the war (Kesternich et al, 2014). We also make extensive use of external data on amounts of calories available in different regions of Germany in the post-war period.…”
mentioning
confidence: 99%